Measuring Fundamentalism Across the Abrahamic Faiths. - Moaddel, Mansoor; Karabenick, Stuart A. (Journal for the Scientific Study of Religion (John Wiley & Sons, Inc.), 2021)
We develop a scale to measure fundamentalism among the followers of the Abrahamic faiths. The scale is intended to overcome the challenges that beset the comparative analysis of the subject: variability of religious fundamentalist movements historically, cross‐nationally, and across these religions; differences in the definition of fundamentalism, and etymological ambiguity of the term. We conceptualized fundamentalism as a cluster of core orientations toward one's and others' religion. These orientations are categorized into four components: disciplinarian deity, inerrancy or literalism, religious exclusivity, and religious intolerance. Each component is measured by four survey questions. The 16 items make a single fundamentalism scale. We discuss the scale's validity, and then verify its statistical and predictive validity on nationally representative samples from Egypt, Iraq, Israel, Jordan, Lebanon, Pakistan, Saudi Arabia, Tunisia, and Turkey, a total of 24,758 cases.